Verbatim Record of the Twenty-Seventh Meeting (Closed) - Héderváry, Claire de (1957)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): United Nations Special Committee on the Problem of Hungary Witness Q, a member of the Dunapentele Revolutionary Council, who organized and directed the Free Radio of Dunapentele from 31 October to 8 November, made a statement. The committee asked him questions about Dunapentele, the revolutionary council in the city, and the radio station he organized. Witness R, a film director, newspaper correspondent and photographer, first requested the investigation of an incident between himself and a security guard in front of the committee room. He made a statement arguing that the Hungarian government was a prisoner of the Soviets during the revolution. Pál Marer, a student, who worked for Kossuth Radio during the revolution, made a statement about negotiations between a local revolutionary council and the commandant of the Soviet tank corps.